Determination of polyfluoroalkyl substances in biological matrices by chromatography techniques: A review focused on the sample preparation techniques - Review - Perovani, Icaro Salgado; Barbetta, Maike Felipe Santos; Duarte, Leandro Oka; de Oliveira, Anderson Rodrigo Moraes [UNESP] (Elsevier, 2023)
Per- and polyfluoroalkyl substances (PFAS) present interesting features for several applications and have great commercial relevance. However, PFAS bioaccumulate, persist in the environment, and are toxic, so regulating and controlling their use and evaluating the risks of human exposure to them is vital. Liquid chromatography with tandem mass spectrometry (LC–MS/MS) has been employed to analyze PFAS, especially in biomonitoring studies. Unfortunately, these studies have been met with challenges, such as the low PFAS concentrations in the samples, small sample amount, contamination of labware and reagents, and signal suppression due to the sample matrix. A suitable sample preparation method could preconcentrate PFAS in the sample and remove the matrix before chromatographic analysis, thereby helping to overcome these challenges. Moreover, the right sample preparation method could reduce the analysis time and enhance the selectivity and sensitivity achieved with HPLC–MS/MS and other correlated techniques. Solid Phase Extraction (SPE) is the most common sample preparation technique. SPE is usually employed with protein precipitation (PPT) in multistep sample preparation methods. Nevertheless, depending on the sample type and composition, presence of contaminants, and analytes, other sample preparation techniques may be relevant. In this paper, we provide a critical review of the sample preparation techniques applied for PFAS analysis in biological matrices. We exploit the benefits, challenges, and future perspectives of these techniques.
Keywords: Biological matrices; Emerging contaminants; HPLC; LC-MS/MS; PFAS; Sample preparation